Contribution of hybrid Al2O3-water nanofluid and PCM suspension to augment thermal performance of coolant in a minichannel heat sink. (July 2018) - Ho, C.J.; Chen, Wei-Chen; Yan, Wei-Mon; Amani, Pouria
Highlights: Hybrid Al2 O3 -water nanofluid and PCM suspension to augment thermal performance is examined. The cooling performance in minichannel heat sink is examined in details. Hybrid suspension can effectively offer better performance. Abstract: The hybrid suspensions may offer better thermal efficacy than the addition of single type of additives. In this work, we attempted to investigate the simultaneous presence of microencapsulated phase change material (MEPCM) particles and Al2 O3 nanoparticles dispersed in the base fluid (ultra-pure Milli-Q water) as a coolant in a minichannel heat sink. The heat sink used in this research had the dimensions of 1 × 1.5 × 50 mm in width, height, and length. The Reynolds number of the coolant ranged from 133 to 1515 in the presence of various concentrations of additives from 2 to 10 wt%. The results revealed that the implementation of the hybrid suspension can significantly improve the heat transportation in the minichannel heat sink (Mini-CHS) compared to the base fluid, due to the cooperative contributions of the superb thermal conductivity of nanoparticles and the latent heat adsorption by phase change particles. However, the performance of the hybrid suspension was highly dependent on the Reynolds number. For instance, it was found that the pure nanofluid outperforms the hybrid suspension at high Reynolds number. The hybrid suspension can effectively offer better performance by wisely adjusting the Reynolds number, and concentrations of nanoparticles and MEPCM particles for a given heat flux.